Integrating science on Xanthomonadaceae for sustainable plant disease management in Europe - Costa, Joana; Pothier, Joël F.; Boch, Jens; Stefani, Emilio; Jacques, Marie‐Agnès; Catara, Vittoria; Koebnik, Ralf (Molecular plant pathology, 2021)
[...]their study was considered of utmost importance for the European Community and beyond. Another genetically related pathogen, Xylella fastidiosa, the causal agent of various economically important diseases, such as Pierce's disease of grapes (PD), citrus variegated chlorosis (CVC), and olive quick decline syndrome (OQDS), has also been covered recently (Rapicavoli et al., 2018). [...]this pathogen was the subject of a Focus Issue in the APS journal Phytopathology (Almeida et al., 2019). Members of this species cause bacterial blight and bacterial spot on important crops (e.g., artichoke, carrot, lettuce, tomato), ornamentals (e.g., ivy, pelargonium), and wild plants (e.g., dandelion). [...]X. hortorum strains have also been isolated from nonprimary symptomatic host plants such as peony, lavender, pot marigold, and avocado.